Green IT adoption: Lessons from the Philippines business process outsourcing industry - Hernandez, Alexander A. (Animo Repository, 2016)
Technology (GIT) refers to using information technology in ways that help to reduce environmental impacts including the use of energy more efficiently and reducing waste. To date, however, few studies attempt to provide a holistic understanding of GIT adoption in developing countries, which GIT plays a significant role in achieving a sustainable environment and economic performance. This paper explores the practices, processes and enablers in GIT adoption within the Philippines Business Process Outsourcing Industry (BPO). The authors used the revelatory multiplecase study as a research approach in understanding GIT adoption in BPO organizations. They found five areas of GIT adoption covering IT procurement, IT applications as low carbon enabler, working environment, data center and IT end of life management. Essentially, strategy and governance, processes, structure, people, technology support, and measurement and improvement enabled GIT adoption in BPO organizations. The authors further found that BPO organizations have the strong long-term commitment to environmental sustainability. Copyright © 2016, IGI Global. Green Information